Impacts of Climate on Renewable Groundwater Resources and/or Stream-Aquifer Interactions - Alcalá, Francisco Javier; Pulido-Velázquez, David; Ribeiro, Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book collects seven original contributions in the field of climate and underlying human influences on renewable groundwater resources and/or stream-aquifer interactions. The first contribution introduces the following six ones into the overall framework of the topic. The second contribution assesses the impact of climate change scenarios on land subsidence related to groundwater level depletion in detrital aquifers. The third contribution studies the patterns of river infiltration and the associated controlling factors by using a combination of field investigations and modeling techniques. The fourth contribution introduces a method to improve the modeling of streamflow in high-permeability bedrock basins receiving interbasin groundwater flow. The fifth contribution discusses the role of resilience of hydrogeological systems affected by either climate and/or anthropic actions in order to understand how anticipating negative changes and preserving its services. The sixth contribution analyzes the water balance of wetlands, which are systems highly sensitive to climate change and human action. The seventh contribution identifies groundwater bodies with low vulnerability to pumping to be used as potential buffer values for sustainable conjunctive use management during droughts.